As inter-relações entre pobreza, desigualdade e crescimento nas mesorregiões mineiras, 1970-2000 - Taiana Fortunato Araujo (2007)
This thesis investigates the inter-relationships between poverty, inequality and growth for the 12 middle regions [mesoregions] in Minas Gerais, over the period 1970-2000, focusing on the concept of monetary poverty. Specifically, we analyze how poverty was affected to its direct macroeconomic determinants: growth (average income) and income inequality. In addition, we examine the quality of economy growth in Minas Gerais. That is, if it is pro-poor. At last, we try to answer if the heterogeneneity across mesoregional poverty levels in 2000 is due to differences in the income level or in income inequality. These examinations rely on 1970, 1980, 1991 and 2000 Brazilian Census microdata, for which one applied the compatibilization (normalization) developed by Chein (2006) and later aggregation on the mesoregional division of 2000. Empirically, we decompose mesoregional poverty variation over time and cross-sectional like, applying Shapley Decomposition, and estimate the Pro-poor Growth Index, developed by Kakwani & Pernia (2000). Our results show that over the whole period, and for its decennial-like sub-periods, the variation of the average income was the dominant effect explaining the decline in the proportion of poor and extremely poor for the very first and last decades and the increase for the middle one. The results for the decompositions are sensitive to the elicited poverty index. When Poverty Gap and Poverty Intensity are used, the redistribution component becomes more relevant on explaining poverty and extremely poverty variation. In spite of that, the improvement or worsening in inequality persists less important to explain differences in poverty levels over time for the historically poorest and lowest-income mesoregions (Vale do Rio Doce, Vale do Mucuri, Vale do Jequitinhonha e Norte de Minas). In the 70s, Minas Gerais and its mesoregions experienced a strictly pro-poor growth. During the 80s, the economic recession was pro-rich. In the 90s, growth has a diverse effect among the mesoregions, although it was less pro-poor than in the Milagre Econômico [Economic Miracle] period. If we focus on the extremely poor, growth has a immiserizing effect. At last, the spatial decomposition of mesoregional poverty for 2000 shows that the difference in poverty levels is predominately addressed to the lower average income of the mesoregions when contrasted to Minas Gerais.